Seasonal influenza vaccine policies, recommendations and use in the World Health Organization's Western Pacific Region Original Research - Members of the Western Pacific Region Global Influenza Surveillance and Response System (World Health Organization Regional Office for the Western Pacific, 2013)
Objective: Vaccination is the most effective way to prevent seasonal influenza and its severe outcomes. The objective of our study was to synthesize information on seasonal influenza vaccination policies, recommendations and practices in place in 2011 for all countries and areas in the Western Pacific Region of the World Health Organization (WHO). Methods: Data were collected via a questionnaire on seasonal influenza vaccination policies, recommendations and practices in place in 2011. Results: Thirty-six of the 37 countries and areas (97%) responded to the survey. Eighteen (50%) reported having established seasonal influenza vaccination policies, an additional seven (19%) reported having recommendations for risk groups for seasonal influenza vaccination only and 11 (30%) reported having no policies or recommendations in place. Of the 25 countries and areas with policies or recommendations, health-care workers and the elderly were most frequently recommended for vaccination; 24 (96%) countries and areas recommended vaccinating these groups, followed by pregnant women (19 [76%]), people with chronic illness (18 [72%]) and children (15 [60%]). Twenty-six (72%) countries and areas reported having seasonal influenza vaccines available through public funding, private market purchase or both. Most of these countries and areas purchased only enough vaccine to cover 25% or less of their populations. Discussion: In light of the new WHO position paper on influenza vaccines published in 2012 and the increasing availability of country-specific data, countries and areas should consider reviewing or developing their seasonal influenza vaccination policies to reduce morbidity and mortality associated with annual epidemics and as part of ongoing efforts for pandemic preparedness.